What impacts the performance of large-scale government projects?. Issue 3 (April 2016) - Patanakul, Peerasit; Kwak, Young Hoon; Zwikael, Ofer; Liu, Min
Abstract: Government projects and programs contribute to national growth at a great magnitude. However, records show that they are not well managed, even when project teams follow established project management principles. As a result, this study aimed at identifying key characteristics of government projects and programs, and recommending how they can be used to improve performance. This paper analyzed 39 public projects undertaken in the U.S., UK, and Australia and reviewed officially by the national audit offices and government agencies, including the Los Angeles Metro, London Heathrow's Terminal 5, and the fatal Australia's Homeowner Insulation Program. Based on this analysis the paper suggests six key characteristics, 17 practical recommendations, and six research propositions. These findings can support government project managers to utilize project management approaches according to project characteristics. This paper can support policy makers and government officials in improving the approaches for the management of government projects and programs Highlights: This study was conducted to identify key characteristics of large-scale government projects 39 government projects in the U.S., UK, and Australia were studied. Include transportation and infrastructure, information systems development and deployment, and defense and space projects Project characteristics were identified, practical recommendations suggested and research propositions raised